2008
DOI: 10.1007/s00421-008-0914-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of heart rate variability by estrogen in young women undergoing induction of ovulation

Abstract: Estrogens are involved in the modulation of the cardiovascular system, yet their effects in young women remains largely unknown. Women who undergo ovulation induction treatments attain extremely high estrogen concentrations during a very short time period. The aim of the present study was to evaluate the effects of an acute increase in estrogens on the autonomic nervous system modulation of heart rate variability (HRV). A total of 27 women undergoing ovulation induction and 14 normally menstruating women were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
0
20
2
Order By: Relevance
“…To date, only seven studies (of roughly 49 currently available studies on cardiac vagal activity across the menstrual cycle as suggested by our meta-analysis [28] and a recent review [30]) have reported associations between ovarian hormone levels and cardiac vagal activity, with mixed results [27,[31][32][33][34][35][36]. However, four major methodological and statistical limitations in these studies prevent clear conclusions.…”
Section: Introductionmentioning
confidence: 80%
“…To date, only seven studies (of roughly 49 currently available studies on cardiac vagal activity across the menstrual cycle as suggested by our meta-analysis [28] and a recent review [30]) have reported associations between ovarian hormone levels and cardiac vagal activity, with mixed results [27,[31][32][33][34][35][36]. However, four major methodological and statistical limitations in these studies prevent clear conclusions.…”
Section: Introductionmentioning
confidence: 80%
“…Postmenopausal women taking estrogen replacement therapy have higher HF power than postmenopausal women not taking estrogen (Liu et al, 2003). Also, women have reduced HF power following oophorectomy that is restored to pre-surgical values with estrogen therapy (Mercuro et al, 2000) and women undergoing acute estrogen treatment for ovulation induction have increased HF power compared to before treatment (Weissman et al, 2009). There is less evidence for the influence of progesterone on the autonomic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Both age-related changes as well as gender differences of R-R interval dynamics are likely linked to (pre-) pubertal hormonal changes [17] because hormones such as estrogen and progesterone as well as substantial changes of hormonal levels during induction of ovulation, onset of menopause or estrogen replacement therapy have been associated with alterations of R-R interval dynamics [32][34]. The present results with respect to long-term fractal scaling properties and complexity suggest that pre-puberty and adrenarche (age 7 to 9 years) also have a specific impact on R-R interval dynamics.…”
Section: Discussionmentioning
confidence: 99%